Analysis of harmonic for 12-pulse converter under unbalanced voltage operation due to lightning related voltage sags and short interruption - Boonseng, C.; Kinnares, V. (My University, 2001)
This paper presents a summary of power quality related concerns associated with the applications of 12-pulse converter with dc motor drives in the industrial plants. These concerns include power system harmonic and harmonic distortion under unbalance voltage condition during voltage sags occurrence. The definition proposed focuses on system faults due to lightning. The voltage unbalance causes large unbalance source currents resulting in excessive input current and high distortion. The percentage of total harmonic distortion of input current (THDi) increased approximately 47% at 6 per unit of normal peak current. The measurement and analysis of such events has been performed. Finally, the new phase-angle jump concept based on measured techniques is introduced.
Keywords: Harmonics; Unbalanced; Voltage sags